Penerapan Hukum terhadap anak sebagai pelaku penyalahgunaan Narkotika - Warsiman Warsiman; Jarnawi Hadi Saputra; Anjani Sipahutar (Jurnal Normatif, 2023)
Abuse of narcotics can result in a dependency syndrome if its use and distribution are not monitored. Narcotics abuse encourages illicit trafficking and causes an increase in abuse that is increasingly widespread and has an international dimension. Therefore, efforts to prevent and control narcotics abuse and efforts to eradicate illicit trafficking are needed. General Provisions in the explanation of Law Number 35 of 2009 concerning Narcotics, the definition of narcotics is a substance or medicine that is very useful and necessary for the treatment of certain diseases. However, if it is used not following treatment standards, it can have very detrimental consequences for individuals and society, especially the younger generation. Narcotics etymologically comes from the Greek Narkoum, which means to paralyze or make numb. Narcotics have properties and are useful for use in the medical field, useful for research, and pharmaceutical science. In this era of globalization, some crimes align children as perpetrators of criminal acts and in cases of abuse that are prohibited in criminal law, one of which is the crime of narcotics abuse. In this case, there is a lot of narcotics spread that has penetrated even remote levels of society, touching and highlighting children who still have a low level of thinking as the main targets or victims. Where, without us realizing it, the potential for children to be indirectly involved in the misuse of very dangerous items is due to factors involving adults. In this case, the main factor that triggers the child to face the law in a narcotics case comes from outside himself, including the very minimal attention of parents (family), and also accompanied by social environmental factors. These two factors simultaneously cause children to often fall into crimes which unknowingly lead the child to become involved in narcotics. Of course, this involvement often occurs when children do not yet have maturity in terms of thinking patterns, so there is a very high potential that a crime will occur. Apart from that, there is a culture of joining in and the participation of adults who try to persuade children to commit crimes that are very detrimental to their future